Aerobics: an eﬀective exercise to improve cognition in adults with mild cognitive impairment - Gazbare, Preeti; Tushar J., Palekar; Medhi, Shreya (Wydawnictwo Akademii Wychowania Fizycznego im. Polskich Olimpijczyków we Wrocławiu, 2025)
Introduction. Mild cognitive impairment (MCI) is a transitional stage between normal ageing and dementia, associated with an increased risk of Alzheimer’s disease. Research has shown a decreased risk of cognitive impairment with moderate-intensity exercise. Dance aerobics has a positive eﬀect on cognition in old age. A limited body of evidence suggests a link between aero-bics and cognitive function in middle-aged adults. To test the eﬀect of 12 weeks of dance aerobics on neurocognitive function in 40–60-year-old adults with MCI.Methods. A single-blinded randomized controlled trial was conducted on ﬁfty middle-aged individuals from the community in Pune, India, after institutional ethical approval. The participants aged 40–60 was screened for the inclusion and exclusion criteria. They were randomly allocated into group A – aerobics (intervention) and group B – routine care only (control). A structured aero-bics protocol was given to group A for 12 weeks with 3 sessions/week. Neurocognitive domains like attention, memory, and executive function were assessed using a Neuropsychological Assessment Battery (NAB) at baseline and 12 weeks of inter-vention for both groups.Results. Statistical analysis was done on 50 participants, 25 in each group, with a mean age of 49.6 ± 4.03. The intervention group showed greater improvement in NAB scores where the mean diﬀerence in the attention domain (15.5; 95% CI = 12.93 to 18.02; p < 0.0001), memory domain (7.24; 95% CI = 5.99 to 8.48; p < 0.0001), and executive function (4.7; 95% CI = 3.6 to 5.94; p < 0.0001) was signiﬁcant compared to the control group.Conclusions. Dance aerobics is a potent way to improve neurocognitive function in middle-aged adults with MCI.
Keywords: dance aerobic; neuropsychological assessment battery; mild cognitive impairment